Introducing GitHub actions : automate tasks and dive into triggers, expressions, and more using environment variables. (Apress, 2023)
This video will get you up and running with GitHub Actions, GitHub's DevOps pipeline engine, which will allow you to automate just about any task. Author and trainer Yas Adel Mehraban takes a very practical hands-on approach for you to follow along, getting you up-to-speed on the terminology and then diving into concepts and code to create basic and more complex workflows. From there you learn how to share workflows within your organization and standardize your work using templates. To conclude the video, you will learn about more complex components such as triggers, expressions, contexts and using environment variables and secrets. What You Will Learn Understand core concepts and benefits of DevOps and CI/CD pipelines Use Yaml syntax for your GitHub workflows Run your first GitHub Action workflow Manage complex scenarios such as handling secrets, integrating depending jobs, configuring stages, environments, and adding labels to workflows Share GitHub Actions within an organization and learn about the templates and triggers available Set custom environment variables in your workflow file Understand the different billing options and limitations Who This Video Is For Any developer, system administrator, IT professionals, devops engineer, or cloud architect, who is already familiar with the fundamentals of GitHub repos source control.